PENDIDIKAN PADA ANAK DAN PELATIHAN KADER TENTANG PENCEGAHAN EKSPLOITASI ANAK DI BATU LAYAR - Baiq Nurul Hidayati; Rias Pratiwi Safitri; Anna Layla Salfarina (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2019)
The West Batu Layar village has good economic potential because along the coast has developed business activities in the tourism sector. The West Batu Layar village has development as a tourist area with negative effects wich increase the cases of exploitation children such as prostitutes, harassment and promiscuity. The foundation of Galang Anak Semesta (GAGAS) Mataram with the Down to Zero program organize training for children's rights, reproduction health, and prevention of Commercial Sexual Exploitation in Children (Eksploitasi Seksual Komersial pada Anak/ESKA). But, the medical treatment has not been maximally for prevention and handling of victims. The purpose of this activity is to counseling and training of child health cadres. Method: This activity uses the Community Empowering approach, which is approach activity through a member of the LPAD of West Batu Layar village. Evaluation of the activities is carried out by posttest directly and in writing to the participants present. Results: This activity have formed a team of health care with increasing of knowledge the participants after treatment more than 25%, so this activity can be said to be successful. Conclusion: The formation of health cadres caring for the exploitation of children in the village of batu layar barat amountes to 10 people, with the level of knowledge of participants increased by more than 25% after being carried out counselling for 3 days. It is expected that the formed of the health cadres of children can become health cadres for children who experience exploitation to apply the principle of healthy living.